Study on Heat Generation at Defects in Sonic-IR Method Using Ultrasonic Wave Input via Water - Yui Izumi; Hirotaka Tanabe; Sota Kato; Noboru Kohiyama (Engineering Proceedings, 2024)
Sonic-IR, which detects defects based on the temperature rise due to frictional heating at the defect faces under ultrasonic excitation, has an advantage in the detection of closed defects. However, in the conventional sonic-IR method, an acoustic energy is directly input from an ultrasonic transducer to the test object via an ultrasonic horn, which may give some scratches and deformation to the test object. To avoid such a problem, we have developed a new sonic-IR method using an ultrasonic wave input via water, and the practicability of the proposed method for the detection of fatigue crack has been experimentally demonstrated. This study presents the results of an investigation of the effect of immersion conditions on heat generation at defects in the proposed method.